KONSUMSI TEMBAKAU DAN IMPLIKASINYA TERHADAP PENGELUARAN PANGAN RUMAH TANGGA: PENDEKATAN FRAKSIONAL LOGIT - Eka Rastiyanto Amrullah; Hijriah Mutmainah; Silvia Yuniarti; Ismatul Hidayah; Aris Rusyiana (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Statistika STIS, 2022)
This study uses a national household consumption expenditure dataset (Susenas 2015). This paper examines the implications of tobacco spending on household food consumption in Indonesia. Overall, the results of the study found a negative and significant relationship in almost all household food expenditure groups, only the beverage expenditure group was positive and significant. Tobacco consumption is not only detrimental to smokers themselves because of its direct impact on health, but also has a negative impact on meeting the basic needs of other family members. Tobacco consumption can sacrifice other food consumption expenditures, causing reduced nutritional intake, malnutrition, and worsening household food insecurity